Differentiating Normal from Pathological Brain Ageing Using Standard Neuropsychological Tests - J. Wakefield, Sarah; J. McGeown, William; F. Shanks, Michael; Venneri, Annalena (Current Alzheimer Research, 2014)
To diagnose Alzheimer’s disease (AD) early, tests sensitive to neuropathology and insensitive to normal ageing are of greatest benefit. We used several neuropsychological tests to identify those best suited to distinguishing Mild Cognitive Impairment (MCI) and early AD from normal ageing. Impairments in long-term memory were found in older adults and these were even greater in MCI and AD. Older adults outperformed young controls on category fluency and produced later acquired and less familiar words. Older adults also outperformed both patient groups on this task producing more words which were significantly later acquired, less familiar and less typical. Decline in long-term memory appears nonspecific and in the early stage of AD cannot help the differentiation between normal and pathological brain ageing. Normal ageing has no negative effects on verbal fluency, and impairment on this task signals not only established AD, but also its prodromal MCI stage.
Keywords: Age of acquisition